CALCULATION OF BUILDING STRUCTURES UNDER THE BRIDGE FRAMEWORK SPANS 40 METERS AT THE BRIDGE BUNGKUK PALARAN SAMARINDA CITY - SIEH, PO (KURVA S JURNAL MAHASISWA, 2014)
The bridge is a building that serves as a complement to the road connecting the two ends of the road were cut off by rivers, lakes, valleys, roads, irrigation canals, bays and other roads. Building structure under the bridge has a function to support and continue building styles from the top to the foundation, then the foundation continue to subsoil. It can be said under the bridge structure and stable foundation can determine whether or not a structure that is in it. In general, the lower structure may be the Head Bridge (abutments). The purpose of this study wanted to know the calculation analysis of loading on the abutment, the abutment reinforcement calculation analysis and calculation analysis pile foundation. Analysis loading calculations using paraturan SNI and SNI T T -02-2005 -03-2005 weeks to steel. From process analysis obtained conclusion that needs reinforcing each - each structural element is different, needs reinforcement of diameter 16 mm, 19 mm and 25 mm. For pile foundation used a diameter of 50 cm, a depth of 60 meters of 12mm thick and required 18 for the stake in the foundation.